2019
DOI: 10.3329/jbcps.v37i4.43345
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hemodialysis Adequacy in Patients with End Stage Renal Disease in a Military Hospital of Dhaka, Bangladesh

Abstract: Introduction: The burden of kidney disease patients requiring renal replacement therapy is increasing day by day. Hemodialysis (HD) constitutes the most common form of renal replacement therapy (RRT) worldwide. Determining the adequacy of hemodialysis, Urea kinetic modeling (UKM) is an important tool for this. The aim of this study was to determine hemodialysis adequacy by UKM. Material & Methods: A total 137 patients were sampled in dialysis center of Combined Military Hospital (CMH) Dhaka. This was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Thus, to achieve adequate hemodialysis, it is recommended to increase the frequency of dialysis from two to three sessions per week. 14 There was no significant difference between age, sex, BMI, comorbidities, vascular access and duration of dialysis with adequate hemodialysis based on URR or Kt/V parameters. Similarly, study from Shariati et al that reported no significant difference between age and adequacy of hemodialysis.…”
Section: Discussionmentioning
confidence: 75%
“…Thus, to achieve adequate hemodialysis, it is recommended to increase the frequency of dialysis from two to three sessions per week. 14 There was no significant difference between age, sex, BMI, comorbidities, vascular access and duration of dialysis with adequate hemodialysis based on URR or Kt/V parameters. Similarly, study from Shariati et al that reported no significant difference between age and adequacy of hemodialysis.…”
Section: Discussionmentioning
confidence: 75%